Investigation Of Dynamic Mechanical Properties Of Magnetorheological Elastomer Based On Nickel Zinc Ferrite And Natural Rubber - Hadi, Nur Haslina Nasirah Abdul (2020)
Magnetorheological elastomers (MREs) are a class of composite that consist of elastomeric matrix with embedded magnetic particles. The performance of MREs can be ascribed to viscoelastic properties of rubber matrix, interfacial interaction at the interface between the rubber matrix and magnetic particles as well as additional mechanism through interparticle magnetic particle interaction. In this research, MREs based on natural rubber and waste nickel zinc ferrites were prepared. Individual components in MREs that contribute to the performance and energy absorption of the materials were investigated. MREs with different natural rubber matrix viscosities and industrial waste nickel zinc ferrite were prepared in order to study the effect of viscoelastic properties of rubber matrix on the dynamic and mechanical performance of the materials. The results revealed that the tan δ increased with increasing matrix viscosity over the whole range of frequency and strain amplitude explored. It was also found that the tensile strength and elongation at break increased with increasing matrix viscosity. The scanning electron microscope (SEM) micrographs revealed that the columnar structures became longer and thicker with a decrease in matrix viscosity. However, numerous cavities remained due to particle pull out, suggesting poor interaction between waste nickel zinc ferrite and rubber matrix. For assessing the effect of interfacial interaction between rubber matrix and magnetic particles on dynamic and mechanical performance of the MREs, Bis-(3-triethoxysilylpropyl) tetrasulphane (TESPT) was utilized to modify the surface of nickel zinc ferrite. The content of xviii TESPT was varied at 0, 2, 4, 6, and 8 wt% for the low and high viscosity rubber matrix. The improved interfacial bonding was evidenced by Fourier transform infrared spectroscopy (FTIR), grafting percentage, crosslink density and SEM images. The result revealed that the tan δ improved approximately 30% over the frequency and strain amplitude explored for both low and high viscosity rubber matrix. Stronger interfacial interaction also improved the tensile properties of the MREs and the optimum content of TESPT was found to be at 6 wt%. The effect of interparticle magnetic particle interaction on dynamic and mechanical performance of the MREs was investigated by curing the materials at 0, 100, 150, 165 and 200 mT magnetic field. It was found that the tan δ increased as the magnetic field increased and level off at magnetic saturation point of 165 mT. However, the tensile strength was found to decrease with increasing magnetic field due to the tensile load direction is perpendicular to the magnetic particles alignment.